Detection of Parasitic Contamination in Ready to Eat Fresh Packaged Herbs Sold in Tehran, Iran - Rouhollah Valipour Nouroozi (Shahid Sadoughi University of Medical Sciences, 2015)
Introduction: Consumption of fresh herbs plays a major epidemiological role in the transmission of some parasitic food-borne diseases. Some manufacturers are producing different kinds of fresh packaged ready-to-eat packaged herbs in Iran. Therefore, this study was carried out in order to evaluate the parasitic contamination in ready-to-eat fresh packaged herbs produced by one of major manufacturers of such products in Tehran, Iran. Methods: A total of 200 packages of ready-to-eat fresh herbs were purchased from a distributor in Tehran in Iran during July 2014 to April 2015. Total content of each package was used as the sample, which was placed into an Erlenmeyer flask. Then, the detergent solution was added, and the flask content was shaken. The herbs were removed and the obtained solution was filtered through 0.2 µm filter. The filtrate was discarded, the filter was eluted by detergent solution, and the content was shaken for one minute. The filter was discarded. The solution was centrifuged at 7000 g for 10 minutes, and the sediment was examined via microscopy. Results: In the current study, 8.5% of samples were reported to have parasitic contamination. Cyst and oocyst of Cryptosporidium spp (4%), Giardia spp (3%) and Entamoeba spp (1.5%) were identified in the present study. Conclusion: The study findings highlighted the potentiality of fresh ready-to-eat packaged herbs to serve as a transmission vehicle for parasites. In addition, this study demonstrated the washing method used by manufacturer of this product was not appropriate.